Measure of non-compactness for nonlocal boundary value problems via $ (k, ψ) $-Riemann-Liouville derivative on unbounded domain - Aphithana, Aphirak; Sudsutad, Weerawat; Kongson, Jutarat; Thaiprayoon, Chatthai (AIMS mathematics, 2023)
In this paper, we investigate the existence result for $ (k, ψ) $-Riemann-Liouville fractional differential equations via nonlocal conditions on unbounded domain. The main result is proved by applying a fixed-point theorem for Meir-Keeler condensing operators with a measure of noncompactness. Finally, two numerical examples are also demonstrated to confirm the usefulness and applicability of our theoretical results.